Case study research and applications : design and methods - Yin, Robert K.; Campbell, Donald T. (Donald Thomas), 1916-1996 (California SAGE Publications, 2018)
"[This book] provides a complete portal to the world of case study research. With the integration of 11 applications in this edition, the book gives readers access to ... case studies drawn from a wide variety of academic and applied fields. Ultimately, [this book] will guide students in the ... design and use of the case study research method. New to this edition: includes 11 in-depth applications that show how researchers have implemented case study methods successfully; increases reference to relativist and constructivist approaches to case study research, as well as how case studies can be part of mixed methods projects; places greater emphasis on using plausible rival explanations to bolster case study quality; discusses synthesizing findings across case studies in a multiple-case study in more detail; adds an expanded list of 15 fields that have text or texts devoted to case study research; and sharpens discussion of distinguishing research from non-research case studies. The author brings to light at least three remaining gaps to be filled in the future: how rival explanations can become more routinely integrated into all case study research; the difference between case-based and variable-based approaches to designing and analyzing case studies; and the relationship between case study research and qualitative research."--
Foreword / Donald T. Campbell -- Preface -- Getting started : how to know whether and when to use the case study as a research method -- Designing case studies : identifying your case(s) and establishing the logic of your case study -- Preparing to collect case study evidence : what you need to do before starting to collect case study data -- Collecting case study evidence : the principles you should follow in working with six sources of evidence -- Analyzing case study evidence : how to start your analysis, your analytic choices, and how they work -- Reporting case studies : how and what to compose
Earlier editions called: Case study research : design and methods
Includes bibliographical references and indexes
Keywords: Case method; Social sciences -- Research -- Methodology; Research Design; Social Sciences -- methods